PENGUKURAN PARAMETER KUALITAS UDARA (SO2) DI KABUPATEN SLEMAN DAN BOYOLALI BERBASIS ISPU: STUDI KASUS ERUPSI GUNUNG MERAPI TANGGAL 3 MARET 2020 - Iqbal Aryuda Nugroho, Muhammad; Pangastuti, Atira Indiani; Fauzul Akbar, Muhammad; Haidar Nasik, Daffa’; Hari Saputra, Agung (Jurnal Widya Climago, 2023)
On March 3, 2020 there was an eruption of Mount Merapi with a height of volcanic ash 6000 m above the mountain peak. The distribution of volcanic ash, especially Mount Merapi, can cause various losses, ranging from disruption to air traffic, dead plants, to human health problems. This study aims to determine the distribution of volcanic ash (SO2), concentrations of SO2 before and after the eruption, and its relationship with the value of the Standard Air Pollution Index (ISPU). This study uses the Two Bands Split Windows (TBWS) method. This method is a method that uses the technique of utilizing two channels on the infrared channel from Himawari-8 satellite imagery, namely the IR (10.8 μm) and I2 (12.0 μm) channels to calculate the Brightness Temperature Difference (BTD) value. This study also uses a quantitative method, namely the measurement of the Air Pollution Standard Index (ISPU) by converting units to micrograms/meter3. Not only that, this research also compares spatial data between Himawari-8 data and VAAC Darwin which then validates the distribution of SO2 with ISPU values. The results show that the direction of distribution of volcanic ash from the eruption of Mount Merapi is dominant towards Sleman and Boyolali Regencies with the ISPU score reaching the highest score of 291 in Boyolali District and in Sleman District reaching a value of 209. The scale is included in the very unhealthy category so that it can increase health risks in the number of segments of the population exposed.